BPA and phthalate fate in a sewage network and an elementary river of France. Influence of hydroclimatic conditions. (January 2015) - Tran, Bich Chau; Teil, Marie Jeanne; Blanchard, Martine; Alliot, Fabrice; Chevreuil, Marc
Highlights: BPA and phthalates were characterized simultaneously in a sewage network and a river. WWTP removal occurred for BPA by degradation and for phthalates by decantation. The impact of the WWTP discharge for both pollutants upon river quality was proven. Opposite variations of BPA and phthalates with the hydro-climatic cycle were shown. Abstract: Our purpose was to characterize the fate of bisphenol A (BPA) and phthalate contamination simultaneously in a sewage network and a watercourse, in relation with hydrological and climatic conditions. An elementary catchment of the Seine basin, receiving effluents from a wastewater treatment plant (WWTP), was chosen because of its basic hydrological features. BPA and DEHP concentrations in the WWTP inputs were 4 and 33 μg L −1 whereas in the outputs, they were only 0.4 and 2 μg L −1, respectively. Contaminant ratios in the suspended sediment phase of the WWTP inputs ranged from 0.5% to 88%, related to their molecular properties. BPA and phthalates were effectively removed in the WWTP (>90% for both compounds), by degradation and decantation. Upstream of the discharge, river concentrations ranged from 0.002 to 0.175 μg L −1 for BPA and from 0.16 to 0.90 μg L −1 for DEHP. Downstream from the WWTP outputs, concentrations ranged from 0.11 to 0.79 μg L −1 for BPA and from 0.31 μg L −1 to 1.7 μg L −1 for DEHP: the WWTP discharge led to contaminant increases of 3.8 and 2 times, respectively. Far downstream, concentrations were lower ranging from 0.11 to 0.19 μg L −1 for BPA and from 0.36 μg L −1 to 1.1 μg L −1 for DEHP. BPA and phthalates displayed opposite seasonal variations with a decrease for the first one and an increase for the second one during summer. BPA contamination in the Charmoise river derived mainly from the WWTP, while phthalate contamination was attributed to both WWTP discharges and diffuse sources such as atmospheric bulk deposition.